Reimagining global health: From decolonisation to indigenization - Suzanne Hindmarch; Sean Hillier (Taylor & Francis Group, 2023)
ABSTRACTIn the wake of global racial justice and Indigenous sovereignty movements, there have been calls to decolonise global health as an academic discipline and set of policies, programmes, and practices. Identifying these calls for decolonisation of global health as both promising but limited, we argue that global health needs to engage in deeper critical reassessment of its ontological foundations in Western thought and that Indigenous ontologies have an important role to play in deconstructing and reimagining global health. We identify four Western ontological assumptions that are particularly relevant to global health and demonstrate how Indigenous ontologies assist in thinking outside of and beyond these assumptions, offering a path toward a reconstructed Indigenized imagining of global health.